EVALUASI KEBIJAKAN DAN MODEL PENINGKATAN KOMPETENSI GURU SD BERSERTIFIKAT BERBASIS TIK - Handayani, Sri; Purwanti, Dwi (Universitas Negeri Semarang, 2013)
Teacher certification is one of the governmentâs efforts in improving the quality of teachers so that the quality of learning in schools. The research aims to evaluate the policy of increasing the professionalism of teachers and formulate SD increase in competency models that have been certified elementary school teachers in ICT-based Central Java. Results of data analysis showed that the competence of elementary school teachers in Central Java which was certified four indicators covering most of the poor category. Four indicators covering ICT competence and the internet (32.64%), competence scientific papers and seminars (67.5%), competence PTK (45.84%) and competence PBM (85%). in the category of not good. Response to the results of the model formulation is made apparent that the local Department of Education LPMP and ICT training have a lot to give, but all teachers have the desire and commitment to the importance of teachers with good mastery of competencies in supporting teacher professionalism. Therefore the relevant parties in the development of teacher professionalism, LPMP, Ministry of Education and local school authorities should be able to develop improved competency models offered in this study that can be done in cooperation with the local LPTK.